IMPROVING CONCENTRATION IN 4-5 YEAR OLD CHILDREN THROUGH POINTILLISM ACTIVITIES AT LIUNGGUNUNG KINDERGARTEN - Nurmalasari, Siska; Purwani, Anisa; Fijar Anugrah, Yuwan (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This classroom action research (CAR) aims to improve the concentration of early childhood children through art activities using pointillism techniques at Pembina Liunggunung Kindergarten. The background of this research is the low concentration ability of children in group A (aged 4–5 years), as seen from their easily distracted attention and lack of perseverance in completing tasks. This research was conducted in two cycles with four stages, namely planning, implementation, observation, and reflection. The research subjects consisted of 11 children in group A at Pembina Liunggunung Kindergarten. Research data were collected through observation sheets, field notes, and activity documentation. The results showed that pointillism activities could gradually improve the concentration of children in group A. In cycle I, the average concentration level of children reached a sufficient category with a percentage of 60%, while in cycle II, it increased to a good category with a percentage of 82%. This improvement was demonstrated through the children’s ability to maintain focus, their perseverance in making colored dots, and their independence in completing tasks. Thus, it can be concluded that pointillism activities are effective in improving the concentration of early childhood group A at Pembina Liunggunung Kindergarten.